TEACHING ARABIC SCRIPTS AND RELIGIOUS CONVERSION - Bahry, Abdul-Rahman (IAIN Tulungagung, 2019)
The government of the State of Ohio determined to design several mandatory programs in regular classes to help NRC’s female in mates to prepare themselves upon their release back to the community; one of the programs is Islamic teaching. It is a chance to insert and implement the innovated peaceful Islamic propagation (dakwah) beside the conventional one, especially in western countries like the United States of America (USA). The chance for an innovated dakwah is open upon observing that a lot of non-Muslimah in mates were curious about Islam in an inter-religious meeting. The Arabic script classis not a part of mandatory NRC programs, it is voluntary for non-Muslimin mates designed and implemented by the author. They learn to write and pronounce the Arabic alphabet from “alif’ to ‘ya’ within six weeks. This free class is to support the government programs in order to reduce recidivism among in mates, and upon completing this class they are encouraged to attending the Islamic teaching class. This paper is qualitative research using a sociology approach. The data collection for this research is using participative observation(2013-2015), voluntary interview, and documentation; the collected data were analyzed in the descriptive-qualitative method. The effectiveness and efficacy of the research should be measured in a quantity of non-Muslimah in mates who gradually and peacefully convert to become Muslimah after attending the Arabic script class. The benchmark of effectiveness should be affirmed in mathematic formula i.e. the effectiveness is equal to the number of Muslimah converts divided by the total participant time 100; it is (3/9) x 100 = 33.33%. Among 9 non-Muslimah participants of free Arabic script class,3 of them converted to be Muslimah.